University Campuses and Housing Markets: Evidence from Nanjing. Issue 2 (3rd April 2018) - Zhong, Ruijun; Zhao, Wanxia; Zou, Yonghua; Mason, Robert J.
Abstract : China has witnessed unprecedented growth of its universities in recent years. Because they function as a sort of urban quasi-public good, university campuses generate a variety of externalities within surrounding communities, including their impacts on adjacent housing markets. Through an analysis of the case of Nanjing, China, this study attempts to quantify the association between university campuses and housing markets in China and to help policymakers, planners, and community members better understand campus–community relationships more generally. The study yields the following findings. First, university campuses have been capitalized into the housing prices of their neighboring communities in Nanjing. Second, in the proximate communities, university campus spillover benefits involve trade-offs with the amenity values of other public goods. Third, campus capitalization effects vary across different tiers of universities. Based on the empirical results, we offer several policy implications, key among which are that policymakers need to acknowledge and rationally distribute the potential spillover benefits of the campus to multiple stakeholders; campus and residential communities should be planned synergistically to optimize land use efficiency; and universities should be fully engaged with their surrounding communities to maximize mutual benefits.